The quadruple helix versus barriers to local development: The example of ‘dual municipalities’ - Cybulska, Magdalena; Mantey, Dorota; Dziemianowicz, Wojciech (Quaestiones Geographicae, 2024)
The article addresses the issue of local collaborative relationships between groups of different development actors in municipalities, as well as their perception of barriers to development. The study covered Polish municipalities that represent different dimensions of development dualism. The analyses used the results of 629 questionnaires and applied statistical analysis (Mann–Whitney U test and Spearman’s rank correlation). The results indicate that the assessment of the importance of different types of relationships and barriers to development varies within some dualisms. At the same time, certain characteristics specific to certain dimensions of these dualisms can be discerned. The relationship between the importance of cooperation and the types of barriers to development showed no statistical significance or very weak relationships.